Fracture toughness and abrasive wear of (ZrTi)B2–SiC ceramic composites with low-modulus hexagonal boron nitride inclusions - Buyakov A. S. Ales Sergeevich; Marianna L. Lukjyanets; Fotin I. A. Igor Andreevich; Shmakov V. V. Vasily Valerjevich; Burlachenko A. G. Aleksandr Gennadjevich; Rudmin M. A. Maksim Andreevich; Buyakova S. P. Svetlana Petrovna (2025, 2025)
Title screen